Caffeine Associated with Exercise Actions on Glycemic Metabolism and Insulin Resistance in Diabetic Animals - Luiz Augusto da Silva ,; Jéssica Wouk ,; Vinicius Muller Reis Weber ,; Leandro Ricardo Altimari ,; Antônio Carlos Dourado ,; Carlos Ricardo Maneck Malfatti ,; Raul Osiecki, (Journal of Pharmacy and Nutrition Sciences, 2018)
Objective: evaluate glycemic metabolism and its relationship with insulin resistance in diabetic animals after caffeine consumption associated with exercise. Material and Methods: 48 animals, of 60 days, divided in four groups: Control, Diabetic, Control+Exercise, Diabetes+Exercise, Caffeine, Diabetes+Caffeine, Exercise+Caffeine and Diabetes+Caffeine+Exercise. Diabetes model was induced by intraperitoneal administration of 120 mg/kg of alloxan. On the test day, 6 mg/kg of caffeine were administrated 30 minutes before exercise and the animals performed a 60 minutes’ session of predominantly aerobic exercise, using an overload of 6% of their body’s weight. With 90 days old, the animals were submitted to an oral glucose tolerance test (OGTT) to verify their glycemic curve. During thirty days of aerobic exercise and/or caffeine treatment, the animals had their glycemia evaluated. At the end of the period, the OGTT was re-evaluated. So, the animals were sacrificed for biochemical analysis (glucose, muscle glycogen and hepatic) and hormonal (insulin). The animals were trained during 30 days by swimming tank, with 4% of extra weight a 40-minute session, daily. Results: Caffeine treatment increased plasma insulin concentration compared to healthy controls (95%, p <0.05). Insulin resistance also reduced for trained diabetic animals treated with caffeine compared to healthy animals (IRI, OGTT and HOMA-IR). Conclusion: Caffeine and training with aerobic exercise in healthy and diabetic animals’ improve biologic systems, increasing the physical ability of the body to resist situations seeking to adapt the tissues to better function.